Применение геоинформационных технологий для оценки радиационного воздействия штатных и проектных аварийных выбросов - Averin В.; Buzdalkin Константин; Nilova Екатерина (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2010)
The geoinformation model allowing to estimate consequences of radiating incidents within several minutes after data acquisition about size of emission of radioactive substances and results of meteorological condition observations concerning by time and a place of an emergency situation is developed. The estimation of short-term and long-term radiating impact is based on the operative construction of the forecast of radionuclide pollution of ground layer of an atmosphere, the agricultural lands and production, dozes of an external and internal irradiation of agroecosystem objects. The model is identified for an estimation of influence radioactive losses on agroecosystem from regular and emergency emissions from water-water power reactors of the ATOMIC POWER STATION - 2006 on the operative data of external dosimetry service of the atomic power station. Application of geoinformation technologies allows to construct the detailed forecast of radioactive pollution of the agricultural lands, forage reserve, food raw material of animal origin and the cultivated plants having food value, for each elementary site of farmland.